Tinjauan Hadits terhadap Jual Beli dengan Sistem Bal Segel - Dion Andi Fauzen; Febriyeni Febriyeni (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2025)
This research was written because it covers a problem that not many people know about, even people who already know about this problem think about it and don't pay much attention to it by the public. In terms of text, there is not a single hadith argument that explains the position of buying and selling bales of seals, this is one of the factors that many of them take this issue seriously so that many of them buy and sell bales of seals. So the author wants to know in full what the position of buying and selling bales of seals is by reviewing the hadiths that are relevant to this issue and informing the reader that they must be careful in carrying out an act whose position is not stated in the Qur'an and hadith so as not to fell into error. This research is a library research study, using the Maudhu'i method to search for and collect hadiths related to the buying and selling of seal bales, and using a contextualization approach to look for hidden meanings in the hadiths. The result of this research is that buying and selling using the sealed bale system should not be carried out, because it involves buying and selling fruit that is not yet ripe. Because these two types of buying and selling have the same problem, namely that there is no certainty regarding the physical aspect of the goods, nor in terms of the quality of the goods.